Characterization of Leucocin B-KM432Bz from Leuconostoc pseudomesenteroides Isolated from Boza, and Comparison of its Efficiency to Pediocin PA-1 - Makhloufi, Kahina Maya; Carré-Mlouka, Alyssa; Peduzzi, Jean; Lombard, Carine; van Reenen, Carol Ann; Dicks, Leon Milner Theodore; Rebuffat, Sylvie (PLOS ONE, 2013)
A bacteriocin-producing bacterium was isolated from boza and identified as Leuconostoc pseudomesenteroides KM432Bz. The antimicrobial peptide was purified and shown to be identical to other class IIa bacteriocins: leucocin A from Leuconostoc gelidum UAL-187 and Leuconostoc pseudomesenteroides QU15 and leucocin B from Leuconostoc carnosum Ta11a. The bacteriocin was named leucocin B-KM432Bz. Leucocin B-KM432Bz gene cluster encodes the bacteriocin precursor (lcnB), the immunity protein (lcnI) and the dedicated export machinery (lcnD and lcnE). A gene of unknown and non-essential function (lcnC), which is interrupted by an insertion sequence of the IS30 family, is localized between lcnB and lcnD. The activity of leucocin B-KM432Bz requires subunit C of the EIItMan mannose permease, which is the receptor for entry into target cells. The determination of the minimum inhibitory concentrations revealed the lowest values for leucocin B-KM432Bz over Listeria strains, with 4 to 32 fold better efficiency than pediocin PA-1.